Spatio-temporal dynamics of net carbon emissions in China's marine fishery: A provincial-level analysis - Mingming Hu; Shaoqiang Nie; Qin Zhu; Tugui Yuan; Wenxiang Zhang (Results in Engineering)
Marine fisheries act as both carbon sources and carbon sinks, making them an important component in climate change mitigation strategies. This study aims to quantify the temporal trends and identify the main drivers of net CO2 emissions in China’s marine fisheries, providing scientific support for carbon neutrality policies in the sector. An integrated accounting framework, considering the direct/indirect carbon emissions of energy use and carbon sequestration in aquaculture, was developed to assess net CO2 emissions in China’s coastal provinces from 2003 to 2023. Using the Logarithmic Mean Divisia Index (LMDI) method, the net CO2 emissions were decomposed into eight driving factors, including technological, structural, and economic scale effects, and conducted provincial-level comparisons to capture spatial heterogeneity. In 2016, the CO2 emissions peaked and declined due to the improvements of energy efficiency and the carbon-sequestering of aquaculture. The economic scale was identified as the largest driver of emissions growth, whereas the structural optimization and technological progress mitigated this trend. Spatial analysis revealed that provinces dominated by capture fisheries had higher net carbon emission intensities; in contrast, provinces with more advanced aquaculture sectors exhibited greater carbon sequestration capacities, which can partially offset the carbon emissions generated by capture fisheries. This framework provides a systematic approach for net carbon accounting in marine fisheries and supports the formulation of targeted low-carbon strategies at the regional level.